Stereotip Kecantikan Perempuan pada Kampanye #BeautyDiQuity dalam Iklan Luxcrime - Fadila Ariani; Sri Ulya Suskarwati; Zhafran Tsany Yudizon (Warta Ikatan Sarjana Komunikasi Indonesia, 2025)
Abstract - The study aims to analyze stereotypical representations of female beauty in the #BeautyDiQuity campaign for Luxcrime advertisement using Roland Barthes semiotic approach. The main focus is how the stereotype of beauty from the model of #BeautydiQuity campaign, which are people with disability shown with photo and video in Luxcrime social media page Instagram. This research using interpretive paradigm, qualitative methodology research, with Roland Barthes Semiotic data analyze, with three level of meaning: connotation, denotation, and myth as well as using data collection techniques through Kenneth Burke’s Pentad method analysis. The result of the research shows that Luxcrime #BeautyDiQuity campaign successfully create a new ideology about beauty. Beauty is not seen based on stereotype of beauty formed in society, which usually measured by physical perfection, but beauty is also seen from other things such as self-love, self-acceptance, daring to appear different, and all the strengths and weaknesses that women have are the true definition of beauty. Keywords: Semiotic; beauty stereotype; social media; beauty product; campaign